Characterization of organic light emitting diodes containing small molecules blended system / Mohd Arif Mohd Sarjidan - Mohd Arif, Mohd Sarjidan (2011)
Organic light emitting diodes (OLEDs) are the future of solid state light and display. However, the efficiency, lifetime and production method still need to be improved. Recently, small molecules OLEDs (SMOLED) are fabricated using thermal evaporation method which is complicated and expensive. In order to solve the problem, this thesis presents a solution processing method for SMOLED fabrication. A robust technique of spin coating has been used to produce SMOLED and the SMOLED were prepared and characterized in room environment. Alq3 has been selected as a main material in this work. The device shows the highest luminance and current efficiency of 8 cd/m2 and 1.1 cd/A, respectively. The performance of the device is improved by doping Alq3 with an organic blend. N,N’-diphenyl-N,N’-bis(3-methylphenyl)-1,1’-biphenyl-4,4’-diamine (TPD) hole-transporting material (HTM) and 2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole (PBD) electron-transporting material (ETM) were used as organic dopant materials. Significant improvement in the performance of the device was achieved for TPD:PBD:Alq3 blend device with a maximum luminance and a current efficiency of 346 cd/m2 and 2.7 cd/A, respectively. The luminance is more than 40 times brighter than Alq3 OLED device. The turn on voltage of the device also reduces from 10 (pure Alq3) to 5V (blend OLED). The optimization of TPD:PBD:Alq3 blend OLED was performed by a simple annealing process. The best performance of the blend OLED was obtained for the device annealed at 100oC for 10 minutes, with a maximum luminance and current efficiency of 680 cd/m2 and 3.6 cd/A, respectively. Major contribution of this research is the development of a new formula, novel blends to enhance the efficiency of single layer OLEDs. Future work can be focused on the blend ratio and the annealing temperature which are expected to produce a variety of color emission and high efficient device.